Sentimento de pertença de adolescentes na interface com a saúde mental: uma revisão de escopo - Speranza, Marina (2021)
Epidemiological studies have pointed out a high prevalence of psychological distress in adolescents, which have been increasing over the last few years, at the same time that there is a scarcity of research that focuses on elements involved in the production of Mental Health among this population. In order to contribute to the expansion of this debate, the present study adds the variable sense of belonging, which has been identified as an important construct for understanding Mental Health of people in general, especially in adolescence. In this direction, the present study aimed to map and analyze the scientific literature on the theme of sense of belonging of adolescents in its interface with Mental Health. This is a Scoping Review, which adopted the approach proposed by the Joanna Briggs Institute-JBI for scoping reviews as a theoretical framework. The search was carried out in the Web of Science, Scopus, Scielo and BVS databases, and the terms used were “sense of belong*”, teenage*, adolescen*, youth, “mental health” and “well-being”, and their respective correspondents in Portuguese and Spanish. The search in the databases generated a total of 270 results, 21 of which were considered eligible because they addressed, in an articulated way, the three central themes of this review, namely adolescence, Mental Health and a sense of belonging. In addition, a consultation process was carried out on the reference lists of these studies, adding nine additional sources to the sample of the present review, totaling 30 studies in the final sample. It is observed that 247 studies were excluded because they did not respond to the research objectives and/or because they were duplicated in the databases. Regarding the results, the quantitative data were analyzed through quantitative descriptive analyzes and organized in graphs and tables, and the qualitative data, derived from the objectives of the productions found, through the Thematic Analysis. It is pointed out that 23 studies used quantitative methodologies, that more than half of the researches were developed in the school context, and that no productions were found in Latin America. Regarding qualitative data, the following categories of analysis emerged: 1) The centrality of the school in the construction of the sense of belonging of adolescents 2) Sense of belonging and the psychological suffering in adolescents; 3) Sense of belonging as a protective factor for the Mental Health of adolescents; 4) Other factors related to the adolescents' sense of belonging; 5) Validation of scales that assess the sense of belonging. It is observed from the results from the selected productions, that the sense of belonging is related to the adolescents' Mental Health, as it involves the way these individuals engage in their activities and social relationships, also influencing the processes of social participation in the different contexts in which this population circulates. It points out the need for future studies carried out in a qualitative way, especially in a participatory way, encompassing the different contexts in which Brazilian adolescents circulate or have the right to circulate and also the different populations of adolescents.